EDUKASI DAN KONSELING POLA ASUH ORANG TUA MENDUKUNG PROGRAM PENCEGAHAN STUNTING DI KELURAHAN LAPPA - Alawiyah, Desi; Surianti, Surianti; Suriati (Universitas Islam Ahmad Dahlan, 2025)
Stunting is a serious health problem in Indonesia, with a prevalence of 27.67%, far above the WHO standard of less than 20%. This condition is recognized as the